Mudanças climáticas globais e o compromisso pró-ecológico de adolescentes natalenses - Barros, Hellen Chrystianne Lucio (2011)
In recent years, much has been discussed about global climate changes (GCCs), popularly known as global warming. The scientific evidences point out to the influence of human actions for its drastic intensification. Therefore, studies of the psychological aspects involved become relevant. This study aimed at the investigation of the views of adolescents concerning GCCs, and the possible relations between those views and their pro-ecological commitment. Such commitment is measured by willingness for engagement in pro-environmental behaviors; environmentalism attitudes, like ecocentric and anthropocentric; consideration of future consequences; and ecological worldviews. Participants were 348 adolescents who answered a questionnaire containing questions about socio-demographic data, open questions about the practice of environmental care, and about GCCs, and the scales of Ecocentric and Anthropocentric Environmentalism, the Consideration of Future Consequences and the Ecological Worldviews assessment scale. From the inter-relationships between variables, procedures carried out by means of descriptive and correlacional statistics, it was observed that 55% of teenagers said that they did not engage in actions of environmental care, which was associated with apathyanthropocentric, immediatism, and individualism. The consideration of future consequences joined the practice of environmental care, corroborating evidence from the literature. It was evident that views concerning GCCs were superficial; adolescents perceive it as a generic environmental problem, and are confused with other problems such as pollution. This study found no association between views about GCCs and the indicators of pro-ecological commitment, perhaps due to the conceptual confusion about the subject. However, the lack of environmental care actions and other indicators of non-commitment (apathy-anthropocentric, individualism and immediatism) were associated with conceptually poor or incomplete responses (with no indication of cause, consequence or responsibility for the problem), demonstrating diminished knowledge and the failure to consider these issues